The Savings Potential of Sino-Indian Free Trade Agreement within Regional Comprehensive Economic Partnership Initiatives - Wardani, Ranti Yulia; Cooray, Nawalage S. (Journal of Reviews on Global Economics, 2019)
The ASEAN community as an international institution has proposed to strengthen economic development by widening cooperation with other countries through regionalism. ASEAN has proposed RCEP with six ASEAN FTA partners within the region. There is no FTA yet between some of the non-ASEAN member countries such as India and China. This condition has influenced the conclusion of RCEP because of different interest among the major power countries. This paper has examined the FTA saving potential analysis between India and China as two of the major power countries in the RCEP negotiations. The FTA saving potential of India and China will be analyzed by using ex-ante analysis. India and China are having the different interests of the preferential agreement on the tariff. India has high tariffs barrier to protect its domestic market. Furthermore, India has demanded the other members to liberalize their services market through RCEP negotiation. India and China have been seen as a rivalry from the political point of view. Both countries have the biggest GDP among RCEP member countries. Therefore, India and China participation in RCEP development are essential to be maintained. The economic interdependence between India and China could lead to cooperation through RCEP. The savings potential analysis shows the tariffs that could be negotiated between India and China. India has proposed to dismantle tariff up to 20 years. This paper has calculated the projection of maximum saving potential that includes three scenarios in the calculation: 20 years of dismantling tariff, export growth and utilization rate. RCEP has been developed to build a comprehensive mutual agreement and economic benefit among the members through cooperation.